A Quantitative PCR Approach for Recognizing the Functional Genes Involved in the Degradation of Naphthalene Dioxygenase and Polycyclic Aromatic Hydrocarbons in Contaminated Soils - Hanan M. Ali (Journal of Global Pharma Technology, 2016)
Analysis of environmental pollutants is very important aspect; cheap and quick methods to clean-up the environment are required. Therefore, the polycyclic aromatic hydrocarbons (PAHs) and naphthalene dioxygenase (NAH-F/NAH-R) were separated from crude oil from north Al-Rumaila/ Iraq. These compounds were used in different concentrations as degraders that docking the functional genes of each of Aspergillus Niger strain AHBR3, Cladosporium ramotenellum and Penicillium brevicompactum isolate 66 small. The results were showed that the three microorganisms use these compounds as a source of food and energy to degrade the pollutants.Keywords: Pollutants, Polycyclic aromatic hydrocarbons, Aspergillus Niger, Cladosporium ramotenellum, Penicillium brevicompactum